Epistemologi Al-Qur’an: Studi Atas Integrasi Wahyu Dan Akal Dalam Tafsir Kontemporer - Saeed Fayzul Hayat; Achmad Abubakar; Halimah Basri (Tasamuh: Jurnal Studi Islam, 2025)
The issue of the relationship between revelation and reason has again become an important focus in contemporary exegetical studies along with the development of rational and scientific approaches to the Qur'an (Q.S. Al-'Alaq [96]: 1–5). This study aims to uncover the epistemological construction of Qur'anic exegesis that seeks to integrate revelation as a source of transcendental truth and reason as an interpretive instrument in understanding the divine message. This study uses a descriptive qualitative approach with library research methods through content and comparative analysis of classical and modern exegetical works such as Fakhruddin al-Razi, Fazlur Rahman, Nasr Hamid Abu Zayd, Muhammad Syahrur, Quraish Shihab, and Seyyed Hossein Nasr. The results show that the integration of revelation and reason is the foundation for a scientific, religious, and humanistic exegetical paradigm. The novelty of this research lies in the attempt to formulate an integrative epistemological model of interpretation that methodologically synthesizes Seyyed Hossein Nasr's Scientia Sacra concept and Fazlur Rahman's Double Movement theory to build a rational and spiritual interpretation framework. Academically, this research recommends the development of an interpretation curriculum and methodology based on integrative epistemology so that Qur'anic interpretation functions not only as a spiritual source but also as a contextual and adaptive intellectual guide to the challenges of the modern era